Enhancing Historical Thinking through Picture-Based Active Learning and Contextual Teaching in Indonesian Vocational Schools - Mada Sulistiyo Rini; Suwito Eko Pramono; Syaiful Amin (Indonesian Journal of History Education, 2025)
This quantitative study investigates the impact of integrating the Picture and Student Active (PASA) learning model with a Contextual Teaching and Learning (CTL) approach on the historical thinking skills of vocational high school students in Indonesia. Using a multiple regression design with two sample classes, data were collected via questionnaire. Results indicate that the application of the PASA model and CTL approach individually does not guarantee a significant improvement in students' historical thinking. However, CTL plays a crucial mediating role, where its consistent integration with both the picture and student-active components indirectly leads to a significant positive effect. Simultaneously, the combined application of the PASA model and CTL approach has a significant influence, accounting for 52%-64% of the improvement in historical thinking skills, as indicated by the Adjusted R-Square value. This suggests that a synergistic, contextually anchored active learning model is effective in fostering higher-order historical reasoning.